1973
DOI: 10.1021/ic50120a018
|View full text |Cite
|
Sign up to set email alerts
|

Heteropoly 12-metallophosphates containing tungsten and vanadium. Preparation, voltammetry, and properties of mono-, di-, tetra-, and hexavanado complexes

Abstract: Council of Canada. Technical assistance was rendered by Mrs. B. Krizsan and Mrs. A. Salios. P. A. Y. gratefully acknowledges financial support of a MacMillan Family Foundation fellowship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0
1

Year Published

1973
1973
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 2 publications
8
45
0
1
Order By: Relevance
“…[36,37] As a matter of fact, the direct hydrothermal metalation (H 2 O, 150°C) of the lacunary precursor (2 ϫ 10 Ϫ3 ) in the presence of stoichiometric amounts of tungstate, molybdate or vanadate anions, in the first two cases does not lead to products, while in the latter case the disubstituted complex is formed. This conclusion has been reached by ESI-MS analysis of the reaction mixtures, showing, for the vanadium-containing system, the replacement of the reagent signals with two new ion peaks at m/z ϭ 873 and 1313, attributed to [LiHPV 2 W 10 …”
Section: Resultsmentioning
confidence: 99%
“…[36,37] As a matter of fact, the direct hydrothermal metalation (H 2 O, 150°C) of the lacunary precursor (2 ϫ 10 Ϫ3 ) in the presence of stoichiometric amounts of tungstate, molybdate or vanadate anions, in the first two cases does not lead to products, while in the latter case the disubstituted complex is formed. This conclusion has been reached by ESI-MS analysis of the reaction mixtures, showing, for the vanadium-containing system, the replacement of the reagent signals with two new ion peaks at m/z ϭ 873 and 1313, attributed to [LiHPV 2 W 10 …”
Section: Resultsmentioning
confidence: 99%
“…Potassium salt of the heteropolyoxometalates, K5[Hx-2PVxW12-xO40] (x = 4 and 6), were prepared following the known procedure 32 .…”
Section: Syntheses Of Catalysts Potassium Salt Of the Heteropolyoxomementioning
confidence: 99%
“…NPMoV was prepared according to the Pope method 18) . Combustion analysis and ICP measurement found that NPMoV has a mean atomic ratio of N/P/Mo/V = 5.0/1.0/4.0/7.8.…”
Section: Preparation Of Molybdovanadophosphatesmentioning
confidence: 99%